Repairing Infrastructures The Maintenance of Materiality and Power - Henke, Christopher R. (Infrastructures, 2020)
An investigation of the causes and consequences of the strange, ambivalent, and increasingly central role of infrastructure repair in modern life. Infrastructures-communication, food, transportation, energy, and information-are all around us, and their enduring function and influence depend on the constant work of repair. In this book, Christopher Henke and Benjamin Sims explore the causes and consequences of the strange, ambivalent, and increasingly central role of infrastructure repair in modern life. Henke and Sims offer examples, from local to global, to investigate not only the role of repair in maintaining infrastructures themselves but also the social and political orders that are created and sustained through them. Repair can encompass not only the kind of work we most commonly associate with the term but also any set of practices aimed at restoring a sense of normalcy or credibility to the places and institutions we inhabit in everyday life. From cases as diverse as the repair of building systems on a university campus, a conflict over retrofitting a bridge while protecting murals painted on it, and the global challenge posed by climate change, Henke and Sims assemble a range of examples to illustrate key conceptual points about the role of repair. They show that repair is an essential if often overlooked aspect of understanding the broader impact and politics of infrastructures. Understanding repair helps us better understand infrastructures and the scope of their influence on our lives.